Second Order Convergence of the Interpolation based on -Element. Issue 4 (17th November 2016) - He, Ruijian; Feng, Xinlong
Abstract: In this paper, the second order convergence of the interpolation based on -element is derived in the case of d =1, 2 and 3. Using the integral average on each element, the new basis functions of tensor product type is builded up and we can easily extend it to the higher dimensional case. Finally, some numerical tests are made to show the analytical results of the interpolation errors.